Research on Innovation Capability Cultivation Oriented Design-Based Learning: Model and Case of Junior High School Information Technology Curriculum - Peiyuan Lin; Zhe Li (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The cultivation of innovative talents is an important development strategy in China. Especially in the stage of basic education, there is an urgent need for specific instructional strategies for cultivating innovative capability. Based on the theories of "Hands-On Inquiry learning" and Constructionism and teaching practice, this study put forward an innovation capability cultivation oriented design-based learning model in junior high school information technology curriculum. The model has three characteristics: simple teaching links, reverse teaching design and equal teacher-student relationship. It is hoped to provide guidance on teaching operation level for frontline information technology classroom teaching, or for other disciplines', and to provide a reference for international scholars to do the research about constructing instructional models for skill cultivation in the 21st century.